Konsep Evaluasi Dalam Pembelajaran Pendidikan Islam - erna nur ma'sumah (https://ejournal.insuriponorogo.ac.id/, 2024)
In general Islamic education, evaluation is very useful for the world of education. Both students, educators and educational institutions can be used to make educational policies and make decisions for the progress and development of education. Evaluation can also be used to help improve the supervision system and consider policies that will be implemented in the national (Islamic) education system. This research uses library or library research to examine several references, books or other products related to the research carried out to examine the thoughts of characters. Evaluation of Islamic education requires procedures that must be used, including planning, implementation, monitoring implementation, data processing, reporting, and use of evaluation results. Furthermore, in its implementation, several evaluation principles must be kept in mind with the aim of being continuous, objective, thorough or comprehensive. The purpose of the evaluation is to invite educational actors, including students, educators and educational institutions, to make decisions so that Islamic religious education is more focused and conceptualized.